Peningkatan Hasil Belajar Tematik Terpadu Menggunakan Model Problem Based Learning di Kelas V Sekolah Dasar - Wahyuni, Ema; Eliyasni, Rifda (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2023)
This research is motivated by the low learning outcomes of students in integrated thematic learning. The research objective was to improve student learning outcomes by using the Problem Based Learning model in class V SDN 16 Koto Balingka, West Pasaman Regency. This type of research is Classroom Action Research (CAR) using a qualitative and quantitative approach. This research was carried out in two cycles with the stages of Planning, Implementation, Observation, and Reflection. Data collection techniques are Observation, Test, and Non-test by using observation sheets, test sheets and non-test sheets. The research subjects were class V teachers and 23 students. The results of the study on the lesson plans for the first cycle were 76.78%, an increase in the second cycle was 92.85%. The implementation of the first cycle of teacher activities increased by 80.35% in the second cycle by 96.42%. The implementation of the first cycle of student activities increased by 78.5 in the second cycle by 96.42%. The learning outcomes of the first cycle were 77.56%, increasing in the second cycle, namely 90.65%. In conclusion, the Problem Based Learning model can improve student learning outcomes in ape, integrated thematic learning.